2022
DOI: 10.56825/bufbu.2022.4123496
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of first lactation 305 day milk yield from monthly test day milk yield using multiple linear regression model in Jaffarabadi buffaloes

Abstract: The records first lactation monthly test day milk yields of 213 Jaffarabadi buffaloes spread over a period of 24 years (1991 to 2014) maintained at Cattle Breeding Farm, Junagadh Agricultural University, Junagadh were used to predict first lactation 305 day or less milk yield using multiple linear regression model with backward elimination procedure. The data were collected at 30 days interval from 4th day till 304th day post calving. The accuracy of prediction model was calculated by estimating R2-value. Anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…was used to isolate RNA from milk fat samples in the following steps [ 59 ]. 1.5 ml of genezol reagent /0.5 g of milk fat [ 60 ] was added, followed by vortexing for homogenization. The homogenate was kept at RT/5 min, then centrifuged at 12000xg for 10 min at 4 oC.…”
Section: Methodsmentioning
confidence: 99%
“…was used to isolate RNA from milk fat samples in the following steps [ 59 ]. 1.5 ml of genezol reagent /0.5 g of milk fat [ 60 ] was added, followed by vortexing for homogenization. The homogenate was kept at RT/5 min, then centrifuged at 12000xg for 10 min at 4 oC.…”
Section: Methodsmentioning
confidence: 99%
“…In another study, Jafarabadi breeds were used to predict the first lactation at 305 days. A linear regression model was fitted by incorporating all 11 monthly test day milk yield records as a partial lactation yield with different combinations to predict the standard lactation yield as early as possible Analysis carried out revealed that when all the monthly test day records (1 to 11) were incorporated in an equation to predict first lactation 305 day or less milk yield, the accuracy (R 2 value) was maximum with 97.06% (Sharma et al, 2022).…”
Section: Introductionmentioning
confidence: 99%